The influence of obesity-related factors in the etiology of renal cell carcinoma-A mendelian randomization study - Johansson, Mattias; Carreras-Torres, Robert; Scelo, Ghislaine; Purdue, Mark P; Mariosa, Daniela; Muller, David C; Timpson, Nicolas J; Haycock, Philip C; Brown, Kevin M; Wang, Zhaoming; Ye, Yuanqing; Hofmann, Jonathan N; et al. (PLoS medicine, 2019)
BACKGROUND: Several obesity-related factors have been associated with renal cell carcinoma (RCC), but it is unclear which individual factors directly influence risk. We addressed this question using genetic markers as proxies for putative risk factors and evaluated their relation to RCC risk in a mendelian randomization (MR) framework. This methodology limits bias due to confounding and is not affected by reverse causation. METHODS AND FINDINGS: Genetic markers associated with obesity measures, blood pressure, lipids, type 2 diabetes, insulin, and glucose were initially identified as instrumental variables, and their association with RCC risk was subsequently evaluated in a genome-wide association study (GWAS) of 10,784 RCC patients and 20,406 control participants in a 2-sample MR framework. The effect on RCC risk was estimated by calculating odds ratios (ORSD) for a standard deviation (SD) increment in each risk factor. The MR analysis indicated that higher body mass index increases the risk of RCC (ORSD: 1.56, 95% confidence interval [CI] 1.44-1.70), with comparable results for waist-to-hip ratio (ORSD: 1.63, 95% CI 1.40-1.90) and body fat percentage (ORSD: 1.66, 95% CI 1.44-1.90). This analysis further indicated that higher fasting insulin (ORSD: 1.82, 95% CI 1.30-2.55) and diastolic blood pressure (DBP; ORSD: 1.28, 95% CI 1.11-1.47), but not systolic blood pressure (ORSD: 0.98, 95% CI 0.84-1.14), increase the risk for RCC. No association with RCC risk was seen for lipids, overall type 2 diabetes, or fasting glucose. CONCLUSIONS: This study provides novel evidence for an etiological role of insulin in RCC, as well as confirmatory evidence that obesity and DBP influence RCC risk.
Keywords: Insulin; nádory ledvin; Male; inzulin; Obesity; Risk Factors; karcinom z renálních buněk; krevní glukóza; obezita; mendelovská randomizace; Kidney Neoplasms; Genome-Wide Association Study; Diabetes Mellitus, Type 2; mužské pohlaví; diabetes mellitus 2. typu; genetické markery; Mendelian Randomization Analysis; lipidy; lidé; krevní tlak; ženské pohlaví; Humans; Body Mass Index; rizikové faktory; Blood Pressure; Carcinoma, Renal Cell; index tělesné hmotnosti; Lipids; Female; Blood Glucose; Genetic Markers; celogenomová asociační studie